Connectivity in dryland landscapes: shifting concepts of spatial interactions. Issue 1 (1st February 2015) - Okin, Gregory S; Heras, Mariano Moreno-de las; Saco, Patricia M; Throop, Heather L; Vivoni, Enrique R; Parsons, Anthony J; Wainwright, John; Peters, Debra PC
Abstract : Dryland ecosystems are often characterized by patchy vegetation and exposed soil. This structure enhances transport of soil resources and seeds through the landscape (primarily by wind and water, but also by animals), thus emphasizing the importance of connectivity – given its relation to the flow of these materials – as a component of dryland ecosystem function. We argue that, as with the fertile‐islands conceptual model before it, the concept of connectivity explains many phenomena observed in drylands. Further, it serves as an organizing principle to understand dryland structure and function at scales from individual plants to entire landscapes. The concept of connectivity also helps to organize thinking about interactions among processes occurring at different scales, such as when processes at one scale are overridden by processes at another. In these cases, we suggest that state change occurs when fine‐scale processes fail to adjust to new external conditions through resource use or redistribution at the finer scale. The connectivity framework has practical implications for land management, especially with respect to decision making concerning the scale and location of agricultural production or habitat restoration in the world's drylands.